Selective TiO2 Nanolayer Coating by Polydopamine Modification for Highly Stable Ni-Rich Layered Oxides - Kim, Hyeongwoo; Jang, Jihye; Byun, Dongjin; Kim, Hyung-Seok; Choi, Wonchang (WILEY-V C H VERLAG GMBH, 2019)
Ni-rich layered oxides are promising cathode materials for developing high-energy lithium-ion batteries. To overcome the major challenge of surface degradation, a TiO2 surface coating based on polydopamine (PDA) modification was investigated in this study. The PDA precoating layer had abundant OH catechol groups, which attracted Ti(OEt)(4) molecules in ethanol solvent and contributed towards obtaining a uniform TiO2 nanolayer after calcination. Owing to the uniform coating of the TiO2 nanolayer, TiO2-coated PDA-LiNi0.6Co0.2Mn0.2O2 (TiO2-PNCM) displayed an excellent electrochemical stability during cycling under high voltage (3.0-4.5 V vs. Li+/Li), during which the cathode material undergoes a highly oxidative charge process. In addition, TiO2-PNCM exhibited excellent cyclability at elevated temperature (60 degrees C) compared with the bare NCM. The surface degradation of the Ni-rich cathode material, which is accelerated under harsh cycling conditions, was effectively suppressed after the formation of an ultra-thin TiO2 coating layer.
Keywords: ENHANCED ELECTROCHEMICAL PERFORMANCE; LINI0.8CO0.1MN0.1O2 CATHODE MATERIAL; TRANSITION-METAL OXIDE; HIGH CUTOFF VOLTAGE; LI-ION BATTERIES; LINI0.6CO0.2MN0.2O2 CATHODE; HIGH-CAPACITY; LINI1/3CO1/3MN1/3O2; GRAPHENE; NANOPARTICLES